Assessment of single isocenter linear accelerator radiosurgery for metastases and base of skull lesions. (January 2021) - Bossart, Elizabeth; Mellon, Eric A.; Monterroso, Irene; Elsayyad, Nagy; Diwanji, Tejan; Samuels, Stuart; Dogan, Nesrin
Graphical abstract: Highlights: Linacs with HDMLC produce SRS plans comparable to GK. For lesions >1 cm, linacs with standard MLC are able to produce comparable plans. For lesion sizes <1 cm, standard MLC plans are not generally comparable. Abstract: Background: Newer technology for stereotactic radiosurgery (SRS) should be assessed for different multi-leaf collimators (MLC). Objective: Assess plan quality of an automated, frameless, linear accelerator based (linac) planning and delivery system (HyperArc) for SRS using both standard MLC (SMLC) and high definition MLC (HDMLC) compared to a cobalt-60 based SRS system (Gamma Knife, GK). Methods: We re-planned twenty GK Perfexion-treated SRS patients (27 lesions) for HyperArc using SMLC and HDMLC. We assessed plan quality using the following metrics: gradient index (GI), Paddick and RTOG conformity indices (CIPaddick, CIRTOG ), volume receiving half of prescription isodose (PIVhalf ) and maximum dose to 0.03 cc for brainstem, optic chiasm and optic nerves, and V12Gy for brain-GTV. Results: Linac plans had better conformity with HDMLC being most conformal. GK exhibited better GI. PIVhalf demonstrated no statistically significant difference between HDMLC and GK, and SMLC was nominally worse than GK. Mean PIVhalf was generally 0.85 cc larger for SMLC than HDMLC. For TV > 1.0 cc, the relative differences in CIRTOG, GI, and PIVhalf for SMLC vs. HDMLC were less than 21%. For TV less than < 1.0 cc, there were more obvious relative differences for SMLC vs. HDMLC in CIRTOG (mean 146%, max 700%), GI (mean 49%, max 162%), and PIVhalf (mean 77%, max 522%). Organ at risk doses were met in all plans. Conclusions: New linac-based plans positively compare to GK plans overall. HDMLC should be strongly considered for treatment of lesions < 1.0 cc given the significant improvements in conformity and PIVhalf over SMLC.